Toxicological effects of the rare earth element neodymium in Mytilus galloprovincialis - Freitas, Rosa (2020)
The wide range of applications of rare earth elements (REE) is leading to their occurrence in worldwide aquatic environments. Among the most popular REE is Neodymium (Nd), being widely used in permanent magnets, lasers, and glass additives. Neodymium–iron–boron (NdFeB) magnets is the main application of Nd since they are used in electric motors, hard disk drives, speakers and generators for wind turbines. Recent studies have already evaluated the toxic potential of different REE, but no information is available on the effects of Nd towards marine bivalves. Thus, the present study evaluated the biochemical alterations caused by Nd in the mussel Mytilus galloprovincialis exposed to this element for 28 days. The results obtained clearly demonstrated that Nd was accumulated by mussels, leading to mussel’s metabolic capacity increase and GLY expenditure, in an attempt to fuel up defense mechanisms. Antioxidant and biotransformation defenses were insufficient in the elimination of ROS excess, resulting from the presence of Nd and increased electron transport system activity, which caused cellular damages (measured by lipid peroxidation) and loss of redox balance (assessed by the ratio between reduced and oxidized glutathione). The results obtained clearly highlight the potential toxicity of REEs and, in particular of Nd, with impacts at cellular level, which may have consequences in mussel’s survival, growth and reproduction, affecting mussel’s population.